2011
DOI: 10.1139/h10-098
|View full text |Cite
|
Sign up to set email alerts
|

Estimated fluid and sodium balance and drink preferences in elite male junior players during an ice hockey game

Abstract: Research in many sports suggests that losing ~2% of body mass (BM) through sweating impairs athletic performance, although this has not been tested in ice hockey players. This study investigated pregame hydration, and on-ice sweat loss, fluid intake, and sodium (Na+) balance of elite male junior players during an ice hockey game. Twenty-four players (2 goalies, 7 defensemen, 15 forwards) volunteered to participate in the study (age, 18.3 ± 0.3 years; weight, 86.5 ±1.6 kg; height, 184.1 ± 1.3 cm). Players were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 35 publications
8
30
0
2
Order By: Relevance
“…We have previously demonstrated that elite ice hockey players lose large amounts of sweat despite practicing in cool ambient temperatures of ϳ11°C (Palmer and Spriet 2008;Palmer et al 2010). Average sweat losses were also high at 3.2 L over a ϳ2.5-h game at ϳ11°C, and many players did not drink enough to prevent BM losses of 1.5% or higher (Logan-Sprenger et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously demonstrated that elite ice hockey players lose large amounts of sweat despite practicing in cool ambient temperatures of ϳ11°C (Palmer and Spriet 2008;Palmer et al 2010). Average sweat losses were also high at 3.2 L over a ϳ2.5-h game at ϳ11°C, and many players did not drink enough to prevent BM losses of 1.5% or higher (Logan-Sprenger et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these findings, ice hockey players ingest little CHO (<15 g·h -1 ) either before or during practices and games (Palmer and Spriet 2008;Logan-Sprenger et al 2011) when the ingestion of 30-60 g CHO·h -1 would be the normal recommendation. In addition, many players do not ingest enough fluid to avoid mild dehydration (Logan-Sprenger et al 2011).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Any urine produced was included in the calculation of sweat loss (Logan-Sprenger et al. 2011, 2013b). …”
Section: Methodsmentioning
confidence: 99%
“…At 45 min, subjects were put on a dry t-shirt and recommenced cycling. Any urine produced was included in the calculation of sweat loss (Logan-Sprenger et al 2011, 2013b.…”
Section: Pre-experimental Protocolmentioning
confidence: 99%